2004
DOI: 10.1073/pnas.0403062101
|View full text |Cite
|
Sign up to set email alerts
|

ATM, a DNA damage-inducible kinase, contributes to activation by high NaCl of the transcription factor TonEBP/OREBP

Abstract: High NaCl activates the transcription factor tonicity-responsive enhancer/osmotic response element-binding protein (TonEBP/OREBP), resulting in increased transcription of several protective genes, including the glycine betaine/γ-aminobutyric acid transporter (BGT1). High NaCl damages DNA, and DNA damage activates ataxia telangiectasia mutated (ATM) kinase through autophosphorylation on Ser-1981. TonEBP/OREBP contains ATM consensus phosphorylation sites at Ser-1197, Ser-1247, and Ser-1367. The present studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
174
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(184 citation statements)
references
References 26 publications
7
174
1
2
Order By: Relevance
“…Hyperosmotic stress enhances translocation of NFAT5 into the nucleus through phosphorylation by signal molecules, such as ATM, Fyn, p38, and protein kinase A (32)(33)(34). In this study, we demonstrated, for the first time, that NFAT5 activity was regulated through the proteasome-mediated proteolysis pathway under cytotoxic conditions, proposing a novel regulatory mechanism of NFAT5 activity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Hyperosmotic stress enhances translocation of NFAT5 into the nucleus through phosphorylation by signal molecules, such as ATM, Fyn, p38, and protein kinase A (32)(33)(34). In this study, we demonstrated, for the first time, that NFAT5 activity was regulated through the proteasome-mediated proteolysis pathway under cytotoxic conditions, proposing a novel regulatory mechanism of NFAT5 activity.…”
Section: Discussionmentioning
confidence: 69%
“…Taken together, it is likely that Dox-induced degradation of NFAT5 is mediated by a proteasome-mediated proteolytic process in an ubiquitinindependent manner. NFAT5 activity is regulated by some protein kinases (32)(33)(34). NFAT5 is phosphorylated under hypertonic condition, and NFAT5 phosphorylation is shown to be a critical event for nuclear translocation, followed by DNA binding (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular event involving active p53 is to stimulate the apoptotic infrastructure by increasing the expression of apoptotic protease-activating factor 1 (APAF-1), a crucial component of the apoptosome (Kinzler and Vogelstein, 1997;Levine, 1997). Functional proteins downstream from the p53 interactive signaling pathways, such as ataxia telangiectasia mutated (ATM) and homolog of ATM (ATR), are central to the DNA damage response (Zhou and Elledge, 2000;Goodarzi et al, 2003;Dodson et al, 2004;Irarrazabal et al, 2004;Kastan, 2004;Yang et al, 2004). Further downstream targets (substrates) of ATM/ATR include the checkpoint protein kinases Chk1 and Chk2 (Ma et al, 1998;Matsuoka et al, 1998;Sanchez et al, 1999;Tominaga et al, 1999).…”
Section: Role Of P53 In Uv Irradiation-induced Dna Damagementioning
confidence: 99%
“…Also, hypertonicity increases transactivation activity of TonEBP͞OREBP, associated with phosphorylation of the C-terminal region containing its transactivation domain (4). Several protein kinases are known to contribute to a hypertonicity-induced increase of TonEBP͞ OREBP transcriptional activity and transactivation, including p38 (5,6), Fyn (5), Ataxia telangiectasia mutated (ATM) (7), and protein kinase A (PKAc) (8), none of them, alone, being sufficient for full activation.…”
mentioning
confidence: 99%
“…High NaCl causes DNA doublestrand breaks (10,11) and, like IR, activates ATM by phosphorylation of S1981 (7). This activation of ATM is necessary for full high NaCl-induced TonEBP͞OREBP transcriptional activity (7).…”
mentioning
confidence: 99%